Pengembangan Media MisBook dalam Pembelajaran Cerita Imajinasi bagi Siswa Kelas VII - Fahriyanti, Alvira Jasmin Eka; Mulyaningtyas, Rahmawati (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Imaginary story learning, that is taught for grade VII on one of the basic competencies 4.4, presents any ideas in the form of imaginary stories orally and literally with spesific attention to the structure, use of language, and oral aspects. Generally,the students often get difficulty in conveying their ideas, both in oral and written form. In addition, the students do not fully understand the material so that it has an impact on the low motivation of students in participating in learning. Therefore, there is a need for media innovation in learning imaginary stories to maximize the learning outcomes. Based on these problems, this article elaborates the development of the MisBook learning media (missions in the book) which is applied in learning imaginary stories. The method used in this research is research and development method. The objectives of this research include (1) developing MisBook media in learning imaginary stories for grade VII students; (2) describe the results of the properness test of the use of the MisBook learning media. The results shows that the MisBook learning media deserves to be applied in learning imaginary stories. The results of the small group trial consisting of 5 seventh grade students shows that the MissBook media is interesting and easy to use. Expert trials shows several things that must be improved from the MisBook media including clarifying the writing of the material to be conveyed; adding the media usage instructions; adding the examples according to theoretical concepts; etc.